APLIKASI PHILOSOPHIES TEORI CARING OLEH JEAN WATSON PADA PASIEN SEBELUM TINDAKAN ESHOPAGOGASTRODUODENOSKOPI DI UNIT ENDOSKOPI RS PRIMAYA BEKASI TIMUR - Bayu Aji Sismanto; Irna Nursanti (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2024)
The effect of the patient's anxiety before performing an esophagogastroduodenoscopy (EGD) action affects the patients' hemodynamics, it can affect the process of such actions when they are performed, usually anxieties are affected by the feeling of being that appears as a result of poor perception of the action to be done, negative perceptions appear often caused by a lack of information about the actions to be performed. Nursing care is very influential to the patient, one of the nursing model theories that can be applied to patients undergoing esophagogastroduodenoscopy (EGD) with the theory of Human Caring by Jean Watson. The nursing process focuses more on health promotion, disease prevention, care for the sick, and physical recovery. The author differentiates the nursing case/orphanage report by applying Jean Watson's model theory using nursery process methods that include the examination, diagnosis, planning, implementation and evaluation of these nurses' orphanages. The result of the implementation that has been done is that the patient feels a change in perception in which the patient experiences a decrease in the level of anxiety after performing a personal caring approach in accordance with Jean Watson's Model Theory.